Hard times : the politics of women's work in computerized environments - Wagner, Ina [Verfasser] (My University, 1995)
As hospital wards are turning into technology-dense environments, the practice of care-giving seems to undergo far-reaching cultural transformations. This article seeks to understand these transformations within a theoretical framework which draws upon an ongoing debate on modernization and the -postmodern condition-. The tensions between feminists-insistence on the presence and vision of particular subjects in geographically, culturally and historically distinct places, articulated in a -politics of location-, and the suspension of subjectivity in technologically supported -time-space- distansiation-set one of the central themes of this article. In a first step, it explores the entrenchment of nurses-work with electronically mediated data, images and connections as- modernization-. The second part looks more explicitly into - politics-behind these technology-mediated cultural transformations of nursing, locating some of the agents behind the development of computer systems for hospitals. (author-s abstract) EDV gestützte Informations- und Kommunikationssysteme verändern räumliche und zeitliche Bezüge in der Krankenpflegearbeit. Der Beitrag befasst sich mit den Veränderungen, die die Computerisierung in Krankenhäusern für diese traditionell als weiblich angesehene Arbeit mit sich bringt. (IAB)
Harte Zeiten : die Politik der Frauenarbeit mit Computern
Keywords: G 2.2.1 Technologisierung; G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); P 1.3 Frauen; EDV-Anwendung; Krankenhaus; Krankenpflege; Frauenberuf; Krankenschwester; Frauen in Einzelberufen; Frauenarbeit; Berufsproblem